PENGARUH FIRM SIZE TERHADAP AGGRESSIVE TAX AVOIDANCE CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR BEI TAHUN 2012-2015 - Widiasmara, Anny; Novitasari, Maya; Hasanah, Karuniawati (Widya Warta, 2018)
According to the Indonesia Investment Coordinating Board (BKPM), the development of investment in Indonesia continues to increase every year. This indicates that multinational corporations that mostly have firmsize values perform aggressive tax avoidance measures in operations. The purpose of this study was (1) to analyze the effect of the firm size on aggressive tax avoidance in manufacturing companies registered in BEI 2012-2015 and (2) to analyze corporate governance as a variable that moderates the firm size to aggressive tax avoidance in manufacturing companies registered in BEI 2012-2015. The data were obtained from www.idx.co.id, Annual Financial Statements. The analysis tool used in this research was Moderated Regression Analysis (MRA) with the formula TA = P0 + P1SIZE + P2LEV + P3ROA + P4SIZE * KIns + P5SIZE * KI + P6SIZE * KA + e) ​​and SPSS 18.00 program. Data collection techniques used were descriptive statistics, classical assumption test, multicollonierity test, heteroscedasticity test, autocorrelation test, MRA. The result of this study showed that the firm size had negative effect on the aggressive tax avoidance, while the corporate governance in this case INST, KI moderated the size of the company against aggressive tax avoidance, and  moderation variables could not moderate firm size with aggressive tax avoidance.